PENGARUH PENAMBAHAN DOSIS UREA DALAM AMONIASI LIMBAH TONGKOL JAGUNG UNTUK PAKAN TERNAK TERHADAP KANDUNGAN BAHAN KERING, SERAT KASAR DAN PROTEIN KASAR - A. Fariani., dkk (BPPT)
The objective of this research was to study the effect of urea dose in corn cob ammoniation on the dry mater , crude fi ber and crude protein. This research was done in two processes. The fi rst process was producing corn cob ammoniation within 7 days.Â The second process was analyzed the nutritive value of corn cob ammoniation. This research used Completely RandomizedÂ Design with 4 treatments and 4 replications were : A (control), B (corn cob+ 2% urea), C (corn cob + 4% urea), D (corn cob + 6% urea), each treatment added with poultry manure 15% of corn cob dry weight. The parameters measured were dry matter, crudefi ber and crude protein. The result showed that all the treatments resulted signifi cantly differences on dry matter, crude fi ber and crude protein. The conclusion of the research was that the treatment by addition urea 4% gave the best result.Key words : Corn Cob, urea dose, poultry manure and ammoniation